Doubly labelled water‐calibrated energy intake associations with mortality risk among older adults. Issue 1 (25th November 2022) - Watanabe, Daiki; Yoshida, Tsukasa; Watanabe, Yuya; Kimura, Misaka; Yamada, Yosuke; ,
Abstract: Background: The body mass index (BMI) is closely related to mortality risk, and energy intake (EI) is essential for maintaining energy balance in weight control. However, self‐reported EI has been shown to lead to a systematic underestimation. Total energy expenditure measured using the doubly labelled water (DLW) method is considered an objective biomarker of EI and the gold standard for its estimation in individuals with stable body weight. We aimed to examine the association between DLW‐calibrated EI and BMI on overall mortality risk in older adults. Methods: A prospective cohort study was performed using data of 8051 (4267 women and 3784 men) Japanese older adults from the Kyoto–Kameoka Study in Japan. Calibrated EI was calculated from the estimated EI using a food frequency questionnaire and equation developed based on DLW. Participants were classified by quartiles based on their EI stratified by sex. BMI was calculated using self‐reported height and body weight. Mortality data were collected between 30 July 2011 and 30 November 2016. Statistical analysis was performed using the multivariable‐adjusted Cox proportional hazard model with a restricted cubic spline. Results: The 8051 participants' mean (standard deviation) age and BMI were 73.5 (6.1) years and 22.6 (3.0) kg/m 2, respectively. The mean (standard deviation) EI with and without calibration was 1909 (145) kcal/day and 1569 (358) kcal/day in women and 2383 (160) kcal/day and 1980 (515) kcal/day in men, respectively. During the median 4.75 years of follow‐up (36 552 person‐years), 661 deaths were recorded. In both women (hazard ratio [HR], 0.63; 95% confidence interval [CI] [0.41, 0.98]) and men (HR, 0.62; 95% CI [0.44, 0.87]), after adjusting for confounders, the top quartile as compared with the bottom calibrated EI quartile showed a negative association with risk of all‐cause mortality. The lowest HR for all‐cause mortality was 1900–2000 kcal/day in women and 2400–2600 kcal/day in men. However, after adjusting for BMI, no significant association was observed between the calibrated EI and the risk of death. These associations could not be confirmed in the uncalibrated EI. The HR for mortality was minimal at a BMI of 23 kg/m 2 in both men and women, with or without adjustment for the calibrated EI. Conclusions: Calibrated EI was negatively associated with mortality risk but not uncalibrated EI. This may be mediated by an increase in body weight over time. Caution is required when interpreting the association between EI and mortality risk without adjusting for self‐reported measurement errors and outcomes.